FEATURES OF LEGAL AND SOCIAL RESPONSE TO DOMESTIC VIOLENCE IN SMALL SETTLEMENT AREAS OF UKRAINE - Litvinova, Iryna; Sadygov, Rustam (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to explore the legal and social particularities of combating domestic violence in small towns of Ukraine, with regard to the challenges posed by the local context. Research methods: to achieve the stated purpose, a combination of general and special scientific methods was used, including the dialectical method, systems approach, analytical methods, and the comparative legal method. Results: the study has revealed that in small towns of Ukraine, access to legal protection and social support for victims of domestic violence remains limited. The current law enforcement practices demonstrate low effectiveness, which is due to both institutional issues and a lack of human and material resources. The analysis of the activities of local self-government bodies and social services indicated a need for improved coordination, clearer distribution of responsibilities, and the development of effective response procedures. Particular attention was given to the current regulatory framework in the sphere of combating domestic violence, especially its adaptation to recent legislative changes. At the same time, local programs were found to have significant potential, which — if properly supported — could serve as a foundation for sustainable community-based prevention mechanisms. Discussion: the results indicate that one of the key obstacles to effectively combating domestic violence in small communities is the low level of public awareness regarding existing protection mechanisms — particularly hotlines, mobile intervention teams, and specialized support services. This is compounded by the influence of local social dynamics: in settings characterized by close interpersonal ties, fear of community judgment, the desire to avoid publicity, and deeply rooted stereotypes about "private family matters" create an environment where violence is silenced. In such conditions, victims often avoid contacting the police, fearing public exposure or lack of proper support. Law enforcement officers, in turn, may favor informal conflict resolution — especially in cases where they have personal ties with both parties involved. This significantly undermines public trust in the legal protection system and fosters a sense of hopelessness among victims. Thus, the situation requires not only improvements in legal instruments but also deeper shifts in social perceptions and interpersonal culture within communities. Raising legal awareness, promoting zero tolerance for violence, and strengthening trust in protection institutions are essential prerequisites for ensuring an effective local-level response. Without such changes, even a formally well-structured system cannot provide adequate protection for victims in small communities.